IoT-enabled system for monitoring and controlling vertical farming operations - Harn Tung Ng; Zhi Kean Tham; Nurul Amani Abdul Rahim; Ammar Wafiq Rohim; Wei Wen Looi; Nur Syazreen Ahmad (International Journal of Reconfigurable and Embedded Systems (IJRES), 2023)
In this paper, we present an internet of things (IoT) powered solution that facilitates effortless monitoring and management of vertical farming operations. Our proposed approach employs cost-effective embedded microcontrollers and sensors to keep a tab on crucial parameters like soil moisture, air humidity, and temperature. The data acquired from these sensors can be accessed through a web page that is compatible with all web browsers and smart gadgets such as mobile phones and tablets. Furthermore, the IoT platform offers users the ability to regulate soil moisture and administer ultraviolet light to plants. The system can bring many benefits such as enabling real-time monitoring and control of environmental conditions, reducing energy consumption, improving scalability and flexibility, and contributing to the sustainable and efficient production of food.